2016
DOI: 10.1007/s10096-016-2784-8
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of New Delhi metallo-beta-lactamase 1 and other carbapenemase-producing Acinetobacter calcoaceticus-baumannii complex among patients in hospitals in Ha Noi, Viet Nam

Abstract: Acinetobacter baumannii is an important cause of multidrug-resistant hospital acquired infections in the world. Here, we investigate the presence of NDM-1 and other carbapenemases among carbapenem-resistant A. baumannii isolated between August 2010 and December 2014 from three large hospitals in Hanoi, Vietnam. We identified 23/582 isolates (4 %) (11 from hospital A, five from hospital B, and seven from hospital C) that were NDM-1 positive, and among them 18 carried additional carbapenemase genes, including se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 30 publications
2
23
0
1
Order By: Relevance
“…A study from another city in Japan showed that 20 CPE were included in two STs (ST2 and ST246), and 17 (85%) were bla OXA‐23 type, similar to results in Gunma University Hospital, Japan . This is different from Vietnam, where NDM is dominant among CRE, similar to Indonesia . Interestingly, a recent study in Jakarta, the capital city of Indonesia, showed that all 14 carbapenem non‐susceptible isolates from an ICU harbored the OXA gene (13 OXA‐66 and one OXA‐68) …”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…A study from another city in Japan showed that 20 CPE were included in two STs (ST2 and ST246), and 17 (85%) were bla OXA‐23 type, similar to results in Gunma University Hospital, Japan . This is different from Vietnam, where NDM is dominant among CRE, similar to Indonesia . Interestingly, a recent study in Jakarta, the capital city of Indonesia, showed that all 14 carbapenem non‐susceptible isolates from an ICU harbored the OXA gene (13 OXA‐66 and one OXA‐68) …”
Section: Discussionmentioning
confidence: 83%
“…Saharman et al . in Jakarta, Indonesia, reported that the isolation rate of CR‐ A. baumannii in the ICU increased alongside the length of hospitalization up to 22 days . This suggests that longer hospitalization increases the risk of transmission of CR‐bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations